Averting Expected Challenges Through Anticipatory Impression Management: A Study of Hospital Billing - Elsbach, Kimberly D.; Sutton, Robert I.; Principe, Kristine E. (Organization Science, 1998)
Existing theory and research on organizational impression management focuses on how spokespersons use remedial tactics, following image-threatening events, to put their organization in the best possible light. By contrast, little theory or research has considered how organizations use impression management tactics to avert undesirable responses to upcoming events. This paper uses a qualitative and inductive study of billing procedures at three large hospitals to develop theory about how organization members use impression management tactics to fend off specific, expected challenges to organizational practices that are ambiguously negative. We found that hospitals use anticipatory impression management tactics to: (1) distract, diminish, or overwhelm patients' attention to hospital charges; and (2) to induce emotions that lead patients to simplify their information processing of those charges. Hospitals appear to use such anticipatory obfuscations both to fend off patients' initial challenges and to prevent their existing challenges from escalating. We discuss these findings in terms of their contributions to theories of symbolic management, social influence, and routine service encounters.